Modelo de previsão hidrológica utilizando redes neurais artificiais: um estudo de caso na bacia do Rio Xingu- Altamira-Pa - SILVA, Arilson Galdino da (Universidade Federal do Pará, 2020)
Knowledge about the extent of riverbed overflow is extremely necessary for the determination of areas at risk. The City of Altamira-PA, located on the banks of the Xingu River, historically suffers from extreme events of floods that provoke floods, causing great damages to the population. Considering the problem, this paper presents a monthly level prediction system of the Xingu River based on neural networks perceptron of multiple layers. For the development of the system, rainfall data were used in the basin and sub-basins of the Xingu River, and SST information (Sea Surface Temperature) from 1979 to 2016. The Satisfactory results demonstrate the great applicability of Artificial Neural Networks to the flood prediction problem, as compared to other methodologies have greater precision in finding solutions for nonlinear problems. For the treatment and selection of the input variables, the correlation approach was used, with the objective of improving the accuracy of the results, thus selecting the best information with their respective lags, in which they are inserted in three prediction scenarios: model with rainfall data, model with sea surface temperature information and application using the SST junction with rainfall. To measure the prediction capacity of the proposed methods, the Mean Squared Error (MSE) and coefficient of determination (R²) values were obtained for the best strategy, using only oceanic variables, SST, being the values 2,99x104 and 0,9991 considering, mainly, the treatment of input values of the Neural Network.